The mist-lining technique: a look into the mechanical performance and the adhesive bond strength of selected lining materials - L. Bertomeu Contreras; L. Fuster López; A. Vicente Escuder (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
Linings pursue the reinforcement of a weak canvas painting, generally by the adhesion of a new fabric. As referred in the specialised literature, among the technical requirements of such a treatment the new structure must present high stiffness and elastic recovery, as well as the use of non-hygroscopic, isotropic and highly reversible materials. This study is intended to evaluate the aspects that govern the adhesion strength of the mist-lining method, a Dutch technique developed in the last decades consisting in spraying an acrylic dispersion a new fabric and its subsequent reactivation by solvent vapours.